A Study on Correlation between Pore Water Pressure, Rainfall and Landslide Occurrence - Suhaimi, D.N.A.A; Selaman, O.S. (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Landslides not only include loss of human lives and properties, but also effect the transportation direct and indirectly. This study focus on the correlation between rainfalls and pore water pressure which lead to landslide event. For this study, the scope of study focuses at Bau, Sarawak whereby lot of landslide event occurs along the road in 2009. Triaxial test is conduct in lab to measure pore water pressure which modeling landslide occurs on 11th January 2009 at KM 72.00 Bau-Lundu Road. From the laboratory test, it can be seen that continuous and heavy rainfall will increase the pore water pressure in soil. When the pore water pressure increase from 809.94 kPa to 829.25 kPa, the strength of the soil will be decrease due to the water content inside the soil. Other than that, correlation between pore water pressure and rainfall can be seen as an exponential relationship by plotting a graph using Microsoft Excel. It indicates that continuous rainfall within 11 days will increase the changes in pore water pressure and causes the soil to be in fully saturation condition. After 27 hours, the soil will be in failure which leads to landslide.